(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The aim of this study was to determine the effectiveness of the pasteurization method on the microbiological quality of goat’s milk stored at different times in the refrigerator. The research was conducted in MarchMay 2020 at the Animal Production Laboratory of the University of Lampung and the Laboratory of the Lampung Veterinary Center. The goat milk sample were colleted from Etawah Grade goats from smallholder farms in Metro City. Milk samples were taken from 20 goats from Etawah Grade in the 2nd and 3rd lactation periods. The goat milk sample used was 9 liters. Goat milk samples were pasteurized using the high temperature short time (HTST) method at a temperature of 72ºC for 15 seconds then cooled and put in a plastic bottle and stored in the refrigerator. This study used a completely randomized design (CRD) with long storage treatment (0 days, 12 days, 24 days, 36 days, 48 days, and 60 days) in the refrigerator. The results showed that pasteurized goat milk with different storage times had no effect on the microbiological quality, namely TPC, S. aureus, coliform bacteria, E. coli, reductase numbers and pH values. The conclusion of this study is that pasteurized goat’s milk using the HTST method is still suitable for consumption until the 60th storage day